Preschool children’s asthma medication: parental knowledge, attitudes, practices, and adherence - Tang, Jianlan; Zhao, Zhihua; Guo, Rong; Niu, Chao; Zhang, Renfei; Wang, Ling; Luo, Nan (Frontiers in Pharmacology, 2024)
This study aimed to analyze the knowledge, attitudes, and practices (KAP) toward asthma medication and adherence among preschool-aged asthmatic children’s parents and explore the factors influencing adherence. This cross-sectional study was conducted between February 2023 and April 2023. Parents of preschool children with asthma were asked to complete the questionnaire containing knowledge, attitude, practice dimensions, and demographic characteristics. The Morisky Medication Adherence Scale (MMAS) was used to investigate adherence. A total of 632 valid questionnaires (154 male and 478 female) were included. Parents showed moderate knowledge (9.49±2.86, 63.27%, possible range: 0-15) and moderate attitudes (26.18±2.51, 74.80%, possible range: 7-35) towards asthma medication, while their practices (27.46±5.26, 91.53%, possible range: 6-30) were proactive; however, medication adherence was low (4.84±1.78, total score: 8). The attitude scores (OR=1.10, 95%CI: 1.01-1.19, P=0.020), practice scores (OR=1.16, 95%CI: 1.12-1.21, P<0.001), and smoking (OR=1.64, 95%CI: 1.14-2.37, P=0.008) were associated with medication adherence. Preschool-aged asthmatic children’s parents showed moderate knowledge, attitudes, and proactive practice toward asthma medication. Continuous training and education programs should be provided for parents to improve asthma medication management in preschool children.